FREQUENCY OF AUTONOMIC NEUROPATHY IN PATIENTS WITH ERECTILE DYSFUNCTION IN DIABETES MELLITUS - Ghafoor, Abdul; Zaidi, Syed Muhammad Hammad; Moazzam, Amena (Journal of Ayub Medical College Abbottabad, 2015)
Background: Among diabetic patients autonomic neuropathy (AN) is one of the most frequent complications. This affects peripheral nervous system and thus results into erectile dysfunction (ED). The main objectives of the study were to determine the frequency of autonomic neuropathy (AN) in diabetic patients with ED and to find out the associated risk factors. Methods: In this descriptive case series, a total 200 consecutive patients of Diabetes Mellitus with erectile dysfunction attended the Department of Endocrinology and Metabolism (DEM), Services Hospital Lahore during three months (from June to August 2013), were included. For assessing erectile dysfunction (ED) and autonomic neuropathy (AN) International Index of Erectile Function (IIEF) and Composite Autonomic Scoring System (CASS) were used respectively. Other factors impacting the autonomic functions in diabetes like duration of diabetes, age of patient, body mass index (BMI), and glycaemic control (HbA1c), hypertension and smoking status were recorded. Results: Average age of the patients was 57.58±9.53 years (95% C.I. 55.54-59.63). Frequency of autonomic neuropathy (AN) in ED patients was 86 (43%). Duration of diabetes Mellitus and BMI were statistically significantly different among patients with severe, moderate and mild autonomic neuropathy. Conclusions: Autonomic neuropathy was very frequent in diabetic patients with erectile dysfunction. The associated risk factors are duration of disease and body mass index.